Biocatalytic Synthesis of γ-glutamyl-L-leucine, a Kokumi-Imparting Dipeptide, by Bacillus licheniformis γ-Glutamyltranspeptidase. Issue 2 (3rd April 2018) - Lee, Yen-Chung; Chi, Meng-Chun; Lin, Min-Guan; Chen, Yi-Yu; Lin, Long-Liu; Wang, Tzu-Fan
ABSTRACT: Several γ-glutamyl compounds are known to have favorable features for a variety of biotechnological and pharmaceutical applications. However, so far only a limited number of γ-glutamyl compounds have been synthesized through γ-glutamyltranspeptidase (GGT). With the help of thin layer chromatography and computer-assisted image analysis techniques, we performed an enzymatic method involving Bacillus licheniformis GGT ( Bl GGT) for the synthesis of γ-glutamyl-L-leucine (γ-Glu-Leu). The optimum conditions for a biocatalytic synthesis of γ-Glu-Leu were determined to be 200 mM glutamine, 200 mM leucine, 50 mM Tris-HCl buffer (pH 9.0), and Bl GGT at a working concentration of 2.0 U/mL. Upon a 5-h incubation of the reaction mixture at 50°C, the product yield could reach approximately 52%. The preparative synthesis of γ-Glu-Leu by Bl GGT was done under optimal conditions at millimol scale level. The reaction products were subjected to mass spectrometry/nuclear magnetic resonance analyses to ensure the successful synthesis of γ-Glu-Leu. Taken together, the present study demonstrates the high potentiality of Bl GGT-catalyzed reaction in the synthesis of γ-glutamyl compounds.